Receptor-mediated endocytosis of epidermal growth factor by rat hepatocytes: receptor pathway (The Rockefeller University Press, 1986)
Substantial amounts of epidermal growth factor (EGF) are cleared from the circulation by hepatocytes via receptor-mediated endocytosis and subsequently degraded within lysosomes. We have used a combined biochemical and morphological approach to examine the fate of the receptor after exposure to EGF. Polyclonal antibodies were prepared against the purified receptor and their specificity established by immunoprecipitation and immunoblotting techniques. The EGF receptor was then localized by immunofluorescence and immunoperoxidase techniques and quantified on immunoblots. In untreated livers, EGF receptor was restricted to the sinusoidal and lateral surfaces of hepatocytes. 2-4 min after exposure of cells to EGF, the receptor was found in small vesicles (i.e., coated vesicles) as well as larger vesicles and tubules at the cell periphery. By 15 min the receptor was found in multivesicular endosomes located near bile canaliculi. Exposure of hepatocytes to EGF also resulted in a rapid loss of receptor protein from total liver homogenates and a decrease in its half-life from 8.7 h in control livers to 2.5 h. This EGF-induced loss of receptors was not observed when lysosomal proteinases were inhibited by leupeptin or when endosome/lysosome fusion was prevented by low temperature (16 degrees C). In the presence of leupeptin, receptor could be detected in structures identified as lysosomes using acid-phosphatase cytochemistry. All these results suggested rapid internalization of EGF receptors in response to ligand and degradation within lysosomes. However, four times more ligand was degraded at 8 h than the number of high-affinity (Kd of 8-15 nM) EGF-binding sites lost, suggesting either (a) high-affinity receptors were recycled, and/or (b) more than 300,000 receptors were available for EGF uptake. We identified and characterized a latent pool of approximately 300,000 low-affinity receptors (Kd approximately 200 nM) that could be separated on sucrose gradients from the plasma membrane pool of approximately 300,000 high- affinity receptors (Kd of 8-15 nM). Despite the differences in their binding affinities, the high- and low-affinity receptors appeared to be structurally identical and were both EGF-dependent protein kinases. In addition, the dynamics of the low-affinity receptors were consistent with a functional role in EGF uptake and delivery to lysosomes.